PROXIMA‐1 beamline for macromolecular crystallography measurements at Synchrotron SOLEIL. (5th May 2021) - Chavas, Leonard M. G.; Gourhant, Patrick; Guimaraes, Beatriz G.; Isabet, Tatiana; Legrand, Pierre; Lener, Robin; Montaville, Pierre; Sirigu, Serena; Thompson, Andrew
Abstract : PROXIMA‐1 at Synchrotron SOLEIL has been run for 12 years as an endstation dedicated to macromolecular crystallography experiments, optimized for anomalous data recording and diffraction studies of large unit‐cell crystals. Abstract : The undulator beamline PROXIMA‐1 at Synchrotron SOLEIL scheduled its first users in March 2008. The endstation is dedicated to biomolecular crystallography experiments, with a layout designed to favour anomalous data recording and studies of crystals with large cell dimensions. In 12 years, the beamline has accommodated 4267 shifts of 8 h and more than 6300 visitors. By the end of 2020, it saw 1039 identified published scientific papers referring to 1415 coordinates deposited in the Protein Data Bank. The current paper describes the PROXIMA‐1 beamline, including the recent specific implementations developed for the sample environment. The setup installed in the experimental station contains numerous beam‐shaping equipment, a chi‐geometry three‐axis goniometer, a single‐photon‐counting pixel‐array X‐ray detector, combined with a medium‐throughput sample exchange robot. As part of a standard experimental scheme, PROXIMA‐1 can also be accessed via `mail‐in' services or remotely.